THE EFFECTIVENESS OF INQUIRY BASED TEACHING TO TEACH GRAMMAR - Eris Isnaini (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
Inquiry-based teaching is a teaching method that focuses on students’ investigation on questions that are challenging in which the questions will lead students to be active and creative to find the answers. The stages are asking, investigating, creating, discussing, and reflecting. This article refers to an experimental study about the effectiveness of Inquiry based teaching to teach grammar at SMK Tamasiswa Sukoharjo, Central Java. The population of this research is the first grade students of SMK Tamansiswa Sukoharjo. The sample of this research consists of two classes; class A was used as the experimental group treated by using inquiry based teaching and class B as the control group treated by using lecture method. The sampling technique used is cluster random sampling. The instrument used to collect the data is grammar mastery test. The data were analyzed by using t-test. Based on the results of the analysis, the findings of this research is inquiry based teaching is more effective than lecture method to teach grammar. Based on the above findings, it can be concluded that inquiry based teaching is an effective method to teach grammar for the first grade students of the SMK Tamansiswa Sukoharjo.  Keywords: Inquiry based Teaching, grammar mastery, lecture method